2001
DOI: 10.1016/s0896-6273(01)00536-0
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Right Parietal Damage Leads to Bilateral Deficit for High-Level Motion

Abstract: Patients with right parietal damage demonstrate a variety of attentional deficits in their left visual field contralateral to their lesion. We now report that patients with right lesions also show a severe loss in the perception of apparent motion in their "good" right visual field ipsilateral to their lesion. Three tests of attention were conducted, and losses were found only in the contralesional fields for a selective attention and a multiple object tracking task. Losses in apparent motion, however, were bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
96
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 54 publications
19
96
2
Order By: Relevance
“…Furthermore, it gives important insights about how the visual system analyzes biological motion. According to our previous study with bilateral and right parietal patients (Battelli et al, 2001) and, confirmed by the present results that include a left parietal lesion subject, low-level motion perception is intact in these patients. They can easily segregate a coherently moving pattern within a high level of background noise, profoundly different from the results for V5 patients reported in the literature (Rizzo et al, 1995;Vaina et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, it gives important insights about how the visual system analyzes biological motion. According to our previous study with bilateral and right parietal patients (Battelli et al, 2001) and, confirmed by the present results that include a left parietal lesion subject, low-level motion perception is intact in these patients. They can easily segregate a coherently moving pattern within a high level of background noise, profoundly different from the results for V5 patients reported in the literature (Rizzo et al, 1995;Vaina et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…2B). Results for JR and JL have previously been reported elsewhere (Battelli et al, 2001) and here they have been contrasted to the left parietal patient JS. The patients were tested both in the left and right visual field and since there was no significant difference between hemifields the data in the graph have been collapsed.…”
Section: Experiments 1: Low-level Motionmentioning
confidence: 67%
See 3 more Smart Citations